(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the outcomes of intrauterine transfusion for fetal anemia at Hanoi Obstetrics and Gynecology Hospital. Materials and Methods: A prospective case series study was conducted on 05 fetuses diagnosed with severe anemia indicated for ultrasound-guided intrauterine transfusion (IUT) at the Fetal Intervention Center, Hanoi Obstetrics and Gynecology Hospital. Results: The mean gestational age at the time of intervention was 29.05 ± 2.43 weeks. The study recorded that 100% of cases achieved target hemoglobin (Hb) levels after a single transfusion. The mean Middle Cerebral Artery Peak Systolic Velocity (MCA-PSV) decreased from 1.91 ± 0.14 MoM pre-intervention to 1.43 ± 0.08 MoM post-intervention. Following the procedure, 4/5 fetuses achieved prolonged survival. The mean gestational age at birth was 29 weeks 6 days ± 23.8 days. The mean 1-minute Apgar score was 5.8 ± 3.35. Poor prognostic factors included: early gestational age at transfusion, fetal hydrops, low pre-transfusion hemoglobin, high MCA-PSV, and the occurrence of procedure-related complications. Conclusion: Intrauterine transfusion is an effective treatment that provides immediate improvement in fetal hematological and hemodynamic status, offering an opportunity to prolong the pregnancy. The results confirm the feasibility of this technique at a tertiary specialized facility while emphasizing the role of early detection and timely intervention before the progression to severe fetal hydrops.